Intercalibration of the Plasma Density Measurements in Earth's Topside Ionosphere. Issue 10 (6th October 2021) - Smirnov, Artem; Shprits, Yuri; Zhelavskaya, Irina; Lühr, Hermann; Xiong, Chao; Goss, Andreas; Prol, Fabricio S.; Schmidt, Michael; Hoque, Mainul; Pedatella, Nicholas; Szabó‐Roberts, Mátyás
Abstract: Over the last 20 years, a large number of instruments have provided plasma density measurements in Earth's topside ionosphere. To utilize all of the collected observations for empirical modeling, it is necessary to ensure that they do not exhibit systematic differences and are adjusted to the same reference frame. In this study, we compare satellite plasma density observations from Gravity Recovery and Climate Experiment (GRACE), Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC), CHAllenging Minisatellite Payload (CHAMP), Swarm, and Communications/Navigation Outage Forecasting System (C/NOFS) missions. Electron densities retrieved from GRACE K‐Band Ranging (KBR) system, previously shown to be in excellent agreement with incoherent scatter radar (ISR) measurements, are used as a reference. We find that COSMIC radio occultation (RO) densities are highly consistent with GRACE‐KBR observations showing a mean relative difference of < 2 %, and therefore no calibration factors between them are necessary. We utilize the outstanding three‐dimensional coverage of the topside ionosphere by the COSMIC mission to perform conjunction analysis with in situ density observations from CHAMP, C/NOFS, and Swarm missions. CHAMP measurements are lower than COSMIC by ∼ 11 % . Swarm densities are generally lower at daytime and higher at nighttime compared to COSMIC. C/NOFS ion densities agree well with COSMIC, with a relative bias of ∼ 7 % . The resulting cross‐calibration factors, derived from the probability distribution functions, help to eliminate the systematic leveling differences between the data sets, and allow using these data jointly in a large number of ionospheric applications. Key Points: A systematic comparison of the plasma density data from CHAMP, C/NOFS, GRACE, COSMIC, and Swarm missions is performed Electron densities retrieved from COSMIC‐RO agree well with GRACE‐KBR observations showing a relative difference of less than 2% Intercalibration factors, allowing to eliminate the systematic offsets between the considered data sets, are presented